Judicial Considerations in the Rejection of Conservatoir Beslag in Land Disputes - Mohammad Rafli Darussalam; Dwi Handayani; Sri Amlinawaty (Faculty of Law, Universitas Muslim Indonesia, 2025)
Abstract: This study examines the urgency of legal protection in resolving land disputes by analyzing judicial considerations and the fulfillment of requirements for the issuance of conservatoir beslag in a court judgment at the appellate level. Land disputes constitute a significant issue as they relate to the certainty of rights, the potential for prolonged conflict, and the vulnerability of communities to document misuse or unlawful possession. The central problems addressed in this research are how judges consider and determine rulings in land dispute cases and whether the requirements for conservatoir beslag have been fulfilled in the case under review. The study employs a normative legal approach to examine relevant legal materials and identify the structure of judicial reasoning. The analysis shows that the judge’s decision is grounded in the principles of justice, legal certainty, and the protection of lawful land rights by assessing valid ownership evidence, the legal standing of the parties, and the relevance of prior decisions that confirm unlawful acts committed by the defendant. The issuance of conservatoir beslag is considered to have met its foundational requirements, supported by sufficient preliminary evidence, a clearly identified disputed object, and reasonable concern over potential transfer of the object that could disadvantage the rightful party. The findings highlight the pivotal role of judges in maintaining the status quo of disputed objects to prevent further harm and strengthen legal protection for legitimate owners. This study recommends enhancing public legal education and strengthening inter-institutional coordination to support the effectiveness of preventive measures in land dispute cases.